The Association Between Wait Times for Colorectal Cancer Treatment and Health Care Costs: A Population-Based Analysis. Issue 2 (February 2020) - Delisle, Megan; Helewa, Ramzi M.; Ward, Mellissa A. R.; Hochman, David J.; Park, Jason; McKay, Andrew
Abstract : BACKGROUND: Health care costs and wait times for colorectal cancer treatment are increasing in Canada, but the association between the 2 remains unclear. OBJECTIVE: This study aimed to determine the association between wait times and health care costs and utilization. DESIGN: This is a population-based retrospective cohort study. SETTING: This study was conducted in Manitoba, Canada. PATIENTS: Patients diagnosed with colorectal cancer between 2004 and 2014 were sorted and ranked into quintiles based on the time from index contact for a colorectal cancer-related symptom to first treatment. MAIN OUTCOME MEASURES: The primary outcome is risk-adjusted health care costs, and the secondary outcomes include health care utilization and overall mortality. RESULTS: We included a total of 6936 patients. Total wait times ranged between 0 and 762 days. In comparison with very short wait times, longer wait times were associated with significantly increased costs (short: mean cost ratio 1.21; 95% CI, 1.10–1.32; moderate: mean cost ratio 1.30; 95% CI, 1.19–1.43; long: mean cost ratio 1.48; 95% CI, 1.33–1.64; and very long: mean cost ratio 1.39; 95% CI, 1.26–1.54). Compared with very short wait times, longer wait times were associated with significantly lower risk of mortality (short: HR, 0.78; 95% CI, 0.71–0.86; moderate: HR, 0.72; 95% CI, 0.65–0.80; long: HR, 0.73; 95% CI, 0.66–0.82; very long: HR, 0.76; 95% CI, 0.68–0.85). The median number of pretreatment radiological and endoscopic investigations and surgeon clinic visits increased over the study period across all wait time categories. LIMITATIONS: This is a nonrandomized, retrospective cohort study with potentially limited generalizability. CONCLUSION: Patients with very short and short wait times are likely those diagnosed with life-threatening complications of colorectal cancer. Outside this window, patients with longer wait times experience increased health care costs and utilization with similar overall mortality. Improved care coordination and patient navigation may help contain the increasing wait times and associated increasing health care costs and utilization. See Video Abstract at http://links.lww.com/DCR/B81 . ASOCIACIÓN ENTRE LOS TIEMPOS DE ESPERA PARA EL TRATAMIENTO DE UN CÁNCER COLORRECTAL Y LOS COSTOS DE ATENCIÓN MÉDICA: UN ANÁLISIS DE POBLACIÓN: ANTECEDENTES: los costos de atención médica y los tiempos de espera para el tratamiento del cáncer colorrectal están aumentando en Canadá, pero la asociación entre los dos sigue sin estar clara. OBJETIVO: determinar la asociación entre los tiempos de espera y los costos y la utilización de la atención médica DISEÑO: un estudio de cohorte retrospectivo basado en la población. MARCO: Manitoba, Canadá PACIENTES: los pacientes diagnosticados con cáncer colorrectal entre 2004-2014 se clasificaron y sub-clasificaron en quintiles según el tiempo desde el primer contacto índice de síntomas relacionados con cáncer colorrectal hasta el primer tratamiento. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario son los costos de atención médica ajustados al riesgo, y los resultados secundarios incluyen la utilización de la atención médica y la mortalidad general. RESULTADOS: Incluimos un total de 6, 936 pacientes. Los tiempos de espera totales oscilaron entre 0-762 días. En comparación con los tiempos de espera muy cortos, los tiempos de espera más largos se asociaron con costos significativamente mayores (Corto: relación de costo promedio 1.21, intervalo de confianza del 95% 1.10-1.32; Moderado: relación de costo promedio 1.30, intervalo de confianza del 95% 1.19-1.43; Largo: media relación de costo 1.48, intervalo de confianza del 95% 1.33-1.64; Muy largo: relación de costo promedio 1.39, intervalo de confianza del 95% 1.26-1.54). En comparación con tiempos de espera muy cortos, los tiempos de espera más largos se asociaron con un riesgo de mortalidad significativamente menor (Corto: razón de riesgo 0.78, intervalo de confianza del 95% 0.71-0.86; Moderado: razón de riesgo 0.72, intervalo de confianza del 95% 0.65-0.80; Largo: peligro cociente 0.73, intervalo de confianza del 95% 0.66-0.82; Muy largo: cociente de riesgos 0.76, intervalo de confianza del 95% 0.68-0.85). La mediana del número de investigaciones radiológicas y endoscópicas previas al tratamiento y las visitas al cirujano aumentaron durante el período de estudio en todas las categorías de tiempo de espera. LIMITACIONES: estudio de cohortes retrospectivo, no aleatorio con generalización potencialmente limitada CONCLUSIÓN: los pacientes con tiempos de espera « muy cortos » y « cortos » son probablemente aquellos diagnosticados con complicaciones potencialmente mortales del cáncer colorrectal. Fuera de esta ventana, los pacientes con tiempos de espera más largos experimentan mayores costos de atención médica y utilización con una mortalidad general similar. La coordinación mejorada de la atención y la navegación del paciente pueden ayudar a contener el aumento de los tiempos de espera y el aumento de los costos y la utilización de la atención médica. Consulte Video Resumen en http://links.lww.com/DCR/B81 . (Traducción—Dr. Edgar Xavier Delgadillo ) Abstract : Supplemental Digital Content is available in the text.